Takedown : inside the hunt for Al Qaeda - Mudd, Philip (Philadelphia, PA : University of Pennsylvania Press, 2013)
On September 11, 2001, as Central Intelligence Agency analyst Philip Mudd rushed out of the Eisenhower Executive Office Building next to the White House, he could not anticipate how far the terror unleashed that day would change the world of intelligence and his life as a CIA officer.
"On September 11, 2001, as Central Intelligence Agency analyst Philip Mudd rushed out of the Eisenhower Executive Office Building next to the White House, he could not anticipate how far the terror unleashed that day would change the world of intelligence and his life as a CIA officer. For the previous fifteen years, his role had been to interpret raw intelligence and report his findings to national security decision makers. But within weeks of the 9/11 attacks, he would be on a military aircraft, flying over the Hindu Kush mountains, en route to Afghanistan as part of the U.S. government's effort to support the fledging government there after U.S. forces had toppled the Taliban. Later, Mudd would be appointed deputy director of the CIA's rapidly expanding Counterterrorist Center and then senior intelligence adviser at the FBI. A first-person account of Mudd's role in two organizations that changed dramatically after 9/11, Takedown sheds light on the inner workings of the intelligence community during the global counterterror campaign. Here Mudd tells how the Al Qaeda threat looked to CIA and FBI professionals as the focus shifted from a core Al Qaeda leadership to the rise of Al Qaeda-affiliated groups and homegrown violent extremism from Europe, the Middle East, and Asia. As a participant in and a witness to key strategic initiatives--including the hunt for Osama bin Laden and efforts to displace the Taliban--Mudd offers an insider's perspective on the relationships between the White House, the State Department, and national security agencies before and after the invasions of Iraq and Afghanistan. Through telling vignettes, Mudd reveals how intelligence analysts understood and evaluated potential dangers and communicated them to political leaders." -- Publisher's description.
The 9/11 aftermath -- A return to Langley -- The spreading threat: moving beyond the core of the Al Qaeda -- The Second War: the intelligence problem of Iraq -- A new view at CIA: Deputy Director of the counterterrorist center -- The years of threat -- Watching threats at home: the FBI calls -- One more transfer: intelligence at the Department of Homeland Security.
Includes index.
Includes bibliographical references and index.
Keywords: Mudd, Philip; United States. -- Central Intelligence Agency -- Officials and employees -- Biography; United States. -- Federal Bureau of Investigation -- Officials and employees -- Biography; Qaida (Organization); Intelligence officers -- United States -- Biography; War on Terrorism, 2001-2009.; Terrorism -- United States -- Prevention; Terrorism -- Government policy -- United States; Mudd, Philip; United States. -- Central Intelligence Agency; United States. -- Federal Bureau of Investigation